Investigation of the process of excitation of dual-frequency vibrations by ball auto-balancer of GIL 42 screen - Филимонихин, Геннадий Борисович; Яцун, Владимир Владимирович (Eastern-European Journal of Enterprise Technologies, 2016)
The 3D model of the upgraded light-duty unbalanced-throw screen GIL 42 with the ball auto-balancer as the exciter of dual-frequency vibrations is developed. Key parameters that affect the stability of dual-frequency vibrations are identified. It is found that the fields of dual-frequency vibrations are relatively large, which allows changing the characteristics of dual-frequency vibrations by changing these parameters. The box mass increase reduces the lower vibration frequency. Herewith, the corrector weights automatically adjust to the box mass change. The mass increase of corrector weights directly increases the amplitude of slow vibrations of the box. The mass increase of the unbalance on the auto-balancer housing directly increases the amplitude of fast vibrations of the box. The rotor speed increase directly increases the speed of fast vibrations of the box. A number of parameters that affect the value of the amplitude of slow vibrations are identified. Since dual-frequency vibrations have two components, arising from the unbalance on the auto-balancer housing and corrector weights respectively, it was decided to examine each component separately. As a result, it is found that the auto-balancer operates as two independent vibration exciters: - the first is formed by corrector weights, and it excites slow vibrations of the box with the natural resonant frequency; - the second is formed by the unbalanced mass on the auto-balancer housing, and it excites fast vibrations of the box with the rotor speed.